Cambodia's Main Challenges in Improving Health among the Poor - World Bank Group (Washington, DC, 2015)
The royal Cambodian government (RCG) has achieved remarkable progress in recent years in reducing the poverty rate by more than half. However, the majority of those escaping from poverty only did so marginally and remain largely near-poor and still highly vulnerable to the slightest of shocks. One of the most critical factors in enabling the poor to escape from poverty, and not only remain non-poor but go on to prosper, lies in ensuring higher levels of health welfare in these households. This is especially important in rural areas, where most of Cambodia s poor reside and where health indicators show a stark divergence with those for urban areas. If poverty is to continue to decline apace, and the gap between rich and poor is to continue to narrow, then the RCG will need to ensure that poor and near-poor people s health care is greatly improved such that they can make the most of the new opportunities in education and employment that are now becoming available. With significant improvements in some health indicators over the past decade, the major challenges in health care going forward are now becoming clearer. These include: making a breakthrough in tackling high levels of child mortality and child malnutrition; addressing equity more effectively in health service provision and health spending, through pro-poor targeted programs and improvements in the coverage and rates of use of health equity funds (HEF); and the improved monitoring of unregulated private providers of medication used by the majority of the poor. In addition, another crucial step forward will be providing adequate financing and ensuring the implementation of Cambodia s first national social protection strategy (NSPS).